Penerapan Sustainable Silent Reading Dalam Meningkatkan Budaya Baca - Suharlik Suharlik (Faculty of Education Universitas Negeri Malang, 2017)
Abstract: The purpose of this research is to know the application of sustainable silent reading (SSR) in improving reading culture in Public Yunior High School 5 Batu (SMP Negeri 5 Batu). The research method used is School Action Research (PTS) with two cycles. The subjects of the study were students and educators of SMP Negeri 5 Batu as many as 98 people. Data were taken by interview, observation, and test. Data were analyzed descriptively. The results showed that the application of sustainable silent reading can improve reading culture in SMP Negeri 5 Batu. In Cycle I with an average value of 62.86 and the average value of the average value of Cycle II 80.39 so from the observation of two cycles there is an increase in journal value of 27.89%. Increase in reading culture can be influenced by internal factors such as interest for reading and external factors, namely motivation and facilities and infrastructure.Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui penerapan sustainable silent reading (SSR) dalam meningkatkan budaya baca di SMP Negeri 5 Batu. Metode penelitian yang digunakan ialah Penelitian Tindakan Sekolah (PTS) dengan dua siklus. Subyek penelitian ialah peserta didik dan tenaga pendidik SMP Negeri 5 Batu sebanyak 98 orang. Data diambil dengan dengan wawancara, observasi, dan tes. Data dianalisis secara diskriptif. Hasil penelitian menunjukkan bahwa penerapan sustainable silent reading dapat meningkatkan budaya baca di SMP Negeri 5 Batu. Pada Siklus I dengan nilai rata-rata 62,86 dan nilai jurnal rata-rata nilai Siklus II 80,39 jadi dari pengamatan dua siklus terdapat kenaikan nilai jurnal sebesar 27,89%. Kenaikan budaya membaca dapat dipengaruhi faktor internal yaitu minat seoarang untuk membaca dan faktor eksternal yaitu motivasi dan sarana dan prasarana.